Programa Nacional de Assistência Estudantil – PNAES e o direito à Educação: do acesso à permanência - Alves, Martins Alves (2025)
This research’s main line of research is Work, Society and Education, at the Programa de Pós-graduação em Educação (PPGED), at Universidade Federal de Uberlândia (UFU), and its aim problematize the Programa Nacional de Assistência Estudantil (PNAES) as strategic action to the promotion of the Brazilian right to third-level education. Over the past few decades, the public higher education is suffering with the neoliberal control effects in the country, sating controversial aspects related to the reassurance of the education right, settled as a social right for the Federal Constitution of 1988, that directly impact the educational social politics, and jeopardizing students access and the length of stay at the public higher education. In this context, the actions of the Programa Nacional de Assistência Estudantil (PNAES), that purpose increase the means of continuity at the superior education in Federal Higher Education Institution (IFES), are also affected, compromising the usufruct of the right of education from students, mostly the ones that are in a vulnerable socio-economic environment. In this sense, this work justifies itself due to the thematic social pertinence about the reinforcement of the social and educational inequality at the Brazilian neoliberal context, where stand out the challenges to student welfare implementation within universities, the focalization in their actions, and the threatening to the length of stay inside the Ifes. Faced with these challenges, the debate about the right of access and continuity at the public third-level education become mandatory, as well as the State role for their implementation. In this view, the research problem consists in comprehend how the PNAES has articulate the student welfare and the right to the public higher education, at Ifes scope. About that problematic, this study was centered in the bibliographical and documental research of a qualitative nature, that draw on literature review of works at the Education and Student Welfare areas, just as on normative related to organization/structure/expansion of Brazilian higher education and student welfare, on normative texts associated with education and third-level education rights. Were used authors as: Minto (2006), Cunha (1988, 2000, 2003, 2007a, 2007b,) Saviani (2010), Silva Jr..; Sguissardi (1999), Crosara; Silva; Oliveira (2020), Crosara; Silva, (2018, 2020), Mocelin (2019), Camenietzki (2019), Cury (2002), Sguissardi (2015b), Kowalski (2012), MacCowan (2015), Sarlet (2011), Zamora (2017), Pereira; Stein (2010), Bering, Boschetti (2016), Boschetti (2010), and others. This text is structured in three sessions. At the first one, the aim was to analyze the social and political context in which university reforms were implemented in Brazil, with a focus on those that occurred in 1968 and between 1990 and 2002. The second section sought to critically examine the higher education politics developed between 2003 and 2016, as well as the National Student Assistance Program (PNAES). The third section was dedicated to the discussion of the right to education and the configuration of the right to public higher education in Brazil, including and analysis of Decree No. 7,234, dated July 19, 2010, which instituted the National Student Assistance Program (PNAES) as a social educational policy aimed at ensuring the permanence of students in Federal Higher Education Institutions (IFES), just as its articulation with the right to third-level education, highlighting its alignment with the neoliberal management of its actions. The research allows the conclusion that the student welfare initiatives relative to the PNAES, while functioning. As an essential strategic action for student retention and the realization of the right to education for many students, also manifest, under neoliberal governance, as a focused, selective policy that remains, therefore, insufficient.